Epizoic arthropods of the Mexican Shrew, Sorex oreopolus (Mammalia: Soricidae) - Montiel Parra, Griselda; Carlos Delgado, Ana Lilia; Paredes-León, Ricardo; Pérez, Tila María (THERYA, 2019)
Shrews (Eulipotyphla: Soricidae) are amongst the most diverse and widely distributed groups of small mammals worldwide. In Mexico, more than 40 species of the genera Sorex, Cryptotis, Megasorex, and Notiosorex have been documented. There is little knowledge about epizoic arthropods of shrews, with 40 species recorded, 28 corresponding to the subclass Acari, and 12 to Insecta. Sorex oreopolus Merriam, 1892, is an endemic species of Mexico, distributed from southwest Jalisco to east Puebla and west Veracruz. This study reports the first records of epizoic arthropods of S. oreopolus. Five specimens of S. oreopolus were collected during 2016 from four sites at La Malinche National Park, state of Tlaxcala. Epizoic arthropods were removed from the pelage of shrews and processed for identification. For each species found in S. oreopolus, ecological parameters of infestation were calculated; for parasitic species, also the degree of host specificity was estimated. A total of 1,194 arthropods were found, corresponding to six mite and one insect taxa. All are new records for this host species. The mites Orycteroxenus soricis (Oudemans 1915) and Pygmephorus horridus Mahunka, 1973 are recorded for the first time in Mexico. The prevalence and abundance of O. soricis was high, while Corrodopsylla lira Traub, 1950 is less prevalent/abundant (Table 1). Epizoic arthropods comprise commensals (Myobiidae), temporary ectoparasites (Trombiculidae) and (Ctenophthalmidae), and phoretic (Glycyphagidae and Pygmephoridae). Seven taxa of epizoic arthropods recorded in this study represent the first record of association with S. oreopolus. The mites O. soricis and P. horridus had already been documented on shrews of the genus Sorex; however, they are recorded for the first time in Mexico, increasing the richness of symbionts of Mexican shrews from 40 to 42 species. Further investigations on the richness of arthropods associated with Mexican shrews are needed, as only seven of 40 species of shrews have been documented, representing 20 % of hosts.